Natural rubber composites with Grits waste from cellulose industry - Bacarin, Giovani B. [UNESP]; Dognani, Guilherme [UNESP]; dos Santos, Renivaldo J. [UNESP]; Meirelles, Maria Genesi; Rodrigues, Thais Fátima; Klauck, Cláudia Regina; Rodrigues, Marco Antônio Siqueira; Jahno, Vanusca Dalosto; Cabrera, Flávio C. [UNESP]; Job, Aldo E. [UNESP] (Springer Nature, 2020)
Tons of industrial residues are daily generated and require management strategies to be correctly disposed or recycled. Therefore, the reuse of organic and industrial wastes as fillers in polymeric composites has gained attention as a new research field. Here, it is demonstrated for the first time the use of Grits waste as filler in natural rubber composites to reuse the eucalyptus kraft pulp residue as well as to decrease the final cost of rubber products by totally or partially replacing the commercial fillers. Untreated waste was employed without pH correction and any coupling agent, while the treated waste had a pH correction and treatment with Dodigen 1611 which is a coupling agent formed by quaternary ammonium salt and increase the residue dispersion or linked it into the polymeric matrix. The pH correction was applied to avoid interference in the vulcanization reaction and it was performed with acetic acid 50% v/v until waste neutralization. Composites with 20 phr of untreated Grits have shown an increase, around 7%, in the stress values when compared to the unfilled natural rubber. However, composites with 20 phr of treated Grits had an increase of 20%. Abrasion loss results show that abrasion resistance tended to decrease when untreated and treated Grits contents are higher than10 phr. An alternative application for the Grits waste composites was in the production of slippers. The produced composites were able to be processed, cut, and molded in an industry of shoes and slippers. The slippers could be well implemented as the composite flexibility was preserved.
Keywords: Filler; Grits; Natural rubber; Reuse